2000
DOI: 10.1111/j.1748-7692.2000.tb00929.x
|View full text |Cite
|
Sign up to set email alerts
|

TEMPORAL VARIABILITY IN FEATURES USED TO PHOTO‐IDENTIFY HUMPBACK WHALES (MEGAPTERA NOVAEANGLIAE)

Abstract: Photographs of 99 humpback whales of known age were analyzed to assess the temporal variability and recognizability of individually distinctive fluke and dorsal fin features used for photo‐identification. Stable features tended to be morphological in nature (dorsal fin shape and edges, the trailing edge of the fluke, and the raised bumps on the caudal peduncle termed “knobs”). Transitory features typically were superficial marks (scarring, scratching, and pigmentation). The variability of several features was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…In New Zealand, Bryde's whales are reported only for the north-eastern coast of the North Island (Baker & Madon 2007, Wiseman 2008) and occur year-round in the Hauraki Gulf (Behrens & Constantine 2008, Wiseman et al 2011). The whales have been ob served throughout the inner Gulf in water depths ranging from 12 to 60 m (Wiseman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Bryde's whales are reported only for the north-eastern coast of the North Island (Baker & Madon 2007, Wiseman 2008) and occur year-round in the Hauraki Gulf (Behrens & Constantine 2008, Wiseman et al 2011). The whales have been ob served throughout the inner Gulf in water depths ranging from 12 to 60 m (Wiseman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although information obtained from photo-identification is highly valuable (Hammond, 1990;Blackmer et al, 2000), processing data in large catalogues can be labour-intensive and subject to human error (Kelly, 2001). Through the use of trials, our study demonstrated the validity (i.e.…”
Section: Discussionmentioning
confidence: 87%
“…The ability to recognize individuals from naturally occurring features has many advantages over conventional marking techniques including: animals are not physically captured, identifiable characteristics are stable over time, and the behaviour of the animal is less likely to be affected by the identification system (Hammond, 1990;Blackmer et al, 2000). Photographic identification, in which researchers photographically capture these natural markings to identify and re-identify individuals, has proven to be a useful tool in long-term monitoring of wild animal populations (Thompson et al, 2000;Forcada and Aguilar, 2003;Bradshaw et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On two occasions humpback whales were seen entering a few hundred meters into the main channel of the lagoon, which is roughly between 15-25 m deep, before turning around. For this species, pigmentation patterns on the ventral surface of the tail fluke, shape of the dorsal fin, and pigmentation and scarring patterns on the sides of the whale can be used to identify individuals uniquely (Friday et al, 2000;Blackmer et al, 2000). Recent attempts to get photographic coverage of humpback whales on Aldabra to allow for such individual recognition are ongoing.…”
Section: Resultsmentioning
confidence: 99%